Reflections on Creemers’ Comprehensive Model of Educational Effectiveness for Reading Literacy: South African evidence from PIRLS 2006 - Surette van staden; Sarah Howie (Perspectives in Education, 2014)
This study reports on a doctoral investigation (Van Staden, 2010) to identify and explain relationships between some major learner- and school-level factors associated with successful reading in Grade 5. South African classrooms are characterised by large variation, with linguistically and socio-economically heterogeneous groups of learners. However, there is a paucity of theoretical frameworks that could explain reading effectiveness in a developing context. For purposes of this study, the South African Grade 5 data from the Progress in International Reading Literacy Study (PIRLS) 2006 were analysed. Hierarchical Linear Modelling (HLM) was applied to determine the effect of a number of explanatory variables at learner- and school-level on reading achievement as outcome variable, while controlling for language. In the absence of a reading effectiveness framework, Creemers’ Comprehensive Model of Educational Effectiveness was used as theoretical point of departure. The framework left the differences in reading scores largely unexplained and could not capture the South African PIRLS 2006 data adequately. The study concludes with reflections on whether Creemers’ model could guide an analysis to explain reading performance and on what further modifications to the model might be required to suit a developing South African context more adequately.